SERVICE READINESS TO WELCOME GROUP GUESTS AT KARAMUNTING HOTEL PALEMBANG: SERVICE READINESS TO WELCOME GROUP GUESTS AT KARAMUNTING HOTEL PALEMBANG - Mustika Permatasari; M. Rian Ahdian Morena; Oneng Setya Harini (Journal Hotspot, 2026)
Karamunting Hotel is a 4-star educational and practical hotel in Palembang. With 105 rooms, the hotel boasts a strategic location in the heart of the Palembang Tourism Polytechnic. This study aims to determine the receptionist's preparation for welcoming group guests, the service provided, and the factors that hinder welcoming group guests at Karamunting Hotel Palembang. The research method used is descriptive qualitative, and data was obtained from interviews with informants, as well as data on the number of group room reservations and standard operating procedures for welcoming guests. The conclusion is that welcoming group guests has not been implemented effectively because service standards, such as luggage handling, are still handled independently by group guests. Furthermore, it is necessary to review the procedures and steps, including standard operating procedures, for welcoming guests.